Long-term outcome of myocardial scarring and deformation with cardiovascular magnetic resonance in out of hospital cardiac arrest survivors. (28th November 2020) - Baritussio, Anna; Biglino, Giovanni; Scatteia, Alessandra; De Garate, Estefania; Dastidar, Amardeep Ghosh; Palazzuoli, Alberto; Harries, Iwan; Strange, Julian W; Diab, Ihab; Bucciarelli-Ducci, Chiara
Abstract: Aims: Cardiovascular magnetic resonance (CMR) is increasingly recognized as a diagnostic and prognostic tool in out of hospital cardiac arrest (OHCA) survivors. After assessing CMR findings early after ventricular fibrillation (VF) OHCA, we sought to explore the long-term outcome of myocardial scarring and deformation. Methods and results: We included 121 consecutive VF OHCA survivors (82% male, median 62 years) undergoing CMR within 2 weeks from cardiac arrest. Late gadolinium-enhancement (LGE) was quantified using the full width at half maximum method and tissue tracking analysis software was used to assess myocardial deformation. LGE was found in 71% of patients (median LGE mass 6.2% of the left ventricle, LV), mainly with an ischaemic pattern. Myocardial deformation was overall impaired and showed a significant correlation with LGE presence and extent ( P < 0.001). A composite end-point of all-cause mortality and appropriate ICD discharge/anti-tachycardia pacing was met in 24% of patients. Patients meeting the end-point had significantly greater LGE extent (8.6% of LV myocardium vs. 4.1%, P = 0.02), while there was no difference with regards to myocardial deformation. Survival rate was significantly lower in patients with LGE ( P = 0.05) and LGE mass >4.4% of the LV identified a group of patients at higher risk of adverse events ( P = 0.005). Conclusions: We found a high prevalence of LGE, early after OHCA, and an overall impaired myocardial deformation. On long-term follow-up both LGE presence and extent showed a significant association with recurrent adverse events, while LV ejection fraction and myocardial deformation did not identify patients with an unfavourable outcome.